Characterization of Turbulent Flow Behind a Transcatheter Aortic Valve in Different Implantation Positions - Pietrasanta, Leonardo; Zheng, Shaokai; De Marinis, Dario; Hasler, David; Obrist, Dominik (Frontiers in Cardiovascular Medicine, 2022)
The development of turbulence after transcatheter aortic valve (TAV) implantation may have detrimental effects on the long-term performance and durability of the valves. The characterization of turbulent flow generated after TAV implantation can provide fundamental insights to enhance implantation techniques. A self-expandable TAV was tested in a pulse replicator and the three-dimensional flow field was extracted by means of tomographic particle image velocimetry. The valve was fixed inside a silicone phantom mimicking the aortic root and the flow field was studied for two different supra-annular axial positions at peak systole. Fluctuating velocities and turbulent kinetic energy were compared between the two implantations. Velocity spectra were derived at different spatial positions in the turbulent wakes to characterize the turbulent flow. The valve presented similar overall flow topology but approximately 8 % higher turbulent intensity in the lower implantation. In this configuration, axial views of the valve revealed smaller opening area and more corrugated leaflets during systole as well as more accentuated pinwheeling during diastole. The difference arose from a lower degree of expansion of the TAV’s stent inside the aortic lumen. These results suggest that the degree of expansion of the TAV in-situ is related to the onset of turbulence and that a smaller and less regular opening area might introduce flow instabilities that could be detrimental for the long-term performance of the valve. The present study highlights how implantation mismatches may affect the structure and intensity of the turbulent flow in the aortic root.